Effects of menstrual cycle on background parenchymal enhancement and detectability of breast cancer on dynamic contrast-enhanced breast MRI: A multicenter study of an Asian population. Issue 110 (January 2019) - Kamitani, Takeshi; Yabuuchi, Hidetake; Kanemaki, Yoshihide; Tozaki, Mitsuhiro; Sonomura, Tetsuo; Mizukoshi, Waka; Nakata, Waka; Shimono, Taro; Urano, Misugi; Yamano, Toshiko; Kato, Fumi; Kuchiki, Megumi; et al.
Highlights: The menstrual cycle affects both BPE and the detectability of breast cancer. The cancer detectability decreases at the secretory phase because of prominent BPE. The menstrual phase as well as the proliferative phase seem to be suitable for breast MRI of premenopausal Asian women. The appropriate phase of the menstrual cycle for breast MRI in Asian women might be longer than those in Western countries. Abstract: Purpose: To evaluate the effect of the menstrual cycle on BPE and cancer detectability in an Asian population. Material and methods: 266 premenopausal patients with regular menstrual cycles from 24 centers were included, and 176 of them were diagnosed by pathology as having breast cancer. Thirty-five patients were examined in the menstrual phase (days 1–4), 105 in the proliferative phase (days 5–14), and 126 in the secretory phase (days 15–30). Measurement of the following signal intensities (SIs) were obtained: breast tissue on the unaffected side on a pre-contrast image (SI1 ) and an early-phase image (SI2 ); the SIs of breast tissue on the affected side on a pre-contrast image (SI3 ) and an early-phase image (SI4 ); and the SIs of breast cancer on a pre-contrast image (SI5 ) and an early-phase image (SI6 ). We calculated the BPE ratio, i.e., (SI2 – SI1 )/SI1 and the cancer/background enhancement ratio (C/B) ratio, i.e., (SI6 – SI5 ) / (SI4 – SI3 ). The BPE was classified as minimal, mild, moderate, or marked, and the cancer detectability was classified as excellent, good, or poor independently by two radiologists. Results: The average C/B ratio was 20.1, 15.7, and 9.1 at the menstrual, proliferative, and secretory phases (p < 0.001). BPE was determined as moderate or marked in 0% and 5.4% at the menstrual phase, 10.3% and 11.0% at the proliferative phase, and 17.5% and 21.7% at the secretory phase by the two observers, respectively (p = 0.01, p = 0.01). The detectability of breast cancer was classified as poor in 0% and 0%, 1.4% and 13.0%, and 8.0% and 22.1% at the menstrual, proliferative, and secretory phases by the two observers, respectively (p = 0.07, p = 0.02). Conclusion: The menstrual phase and the proliferative phase seem to be suitable for breast MRI of Asian women.